Bauran Media Elektronik Terhadap Peningkatan Kepesertaan BPJS Ketenagakerjaan Cabang Makassar - Rahman, Wahyuddin; Achmad Gani, Ackriansyah (Journal of Management Sains (JMS), 2023)
This research was conducted with the aim to know the influence of each variable of electronic media mix consisting of Television media, Radio and internet media significantly to increase participation of BPJS Employment of Makassar Branch, and to know the effect simultaneously or simultaneously variable of electronic media of television media, media radio and internet media to increase participation BPJS Employment Makassar Branch. This study uses questionnaires, literature study and interviews with quality assay data analysis techniques, classical assumption test, multiple linear regression analysis and hypothesis testing. The results of the study found that electronic media consisting of: television media, radio media and internet media have a significant influence on the increase of membership BPJS Employment Branch of Makassar. So the first hypothesis can be accepted. Based on the result of simultaneous test, it is obtained the value of Fcount = 398.637 with the significance of 0.000 with the negligence level of 0.05, so it can be said that the television media, radio media and internet media together influence the increase of membership BPJS Employment Makassar Branch. So the second hypothesis proposed can be accepted and proven true